The Use of Learning Videos to Increase the Activeness of Students on the Content of PPKn Lessons - Irnanita Indayah Kusumadewi (Universitas Sebelas Maret, 2020)
The background of the researchers conducting this research is the lack of use of instructional videos as a medium and the low involvement of students in the learning process. The purpose of this study was to increase the activeness of grade IV students by using video lessons on the PPKn lesson content. This research is a classroom action research (PTK) which is conducted in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the fourth grade students of SD Negeri 03 Cikendung in the 2020/2021 academic year, totaling 20 students. Data collection techniques using observation. The data analysis technique used is the observation data analysis technique. Research shows that the use of instructional videos can increase the activeness of students in the PPKn lesson content, the symbol and meaning of the second Pancasila precepts in class IV SD Negeri 03 Cikendung in the 2020/2021 school year as evidenced by the average percentage of activeness in the first cycle of 60% to 75 % in cycle II and increased to 80%.